Vasoactive-ventilation-renal score and outcomes in infants and children after cardiac surgery - Abhay, Pota; Sharma, Rajesh; Bhan, Anil; Raina, Manan; Vadhera, Ananya; Akole, Romel; Mir, Firdoos Ahmad; Bajpai, Pankaj; Misri, Amit; Srivastava, Swarnika; Prakash, Ved; Mondal, Tanmoy; et al. (Frontiers in Pediatrics, 2023)
Introduction There is a need to index important clinical characteristics in pediatric cardiac surgery that can be obtained early in the postoperative period and accurately predict postoperative outcomes. Methodology A prospective cohort study was conducted in the pediatric cardiac ICU and ward on all children aged <18 years undergoing cardiac surgery for congenital heart disease from September 2018 to October 2020. The vasoactive-ventilation-renal (VVR) score was analyzed to predict outcomes of cardiac surgeries with a comparison of postoperative variables. Results A total of 199 children underwent cardiac surgery during the study period. The median (interquartile range) age was 2 (0.8–5) years, and the median weight was 9.3 (6–16) kg. The most common diagnoses were ventricular septal defect (46.2%) and tetralogy of Fallot (37.2%). At the 48th h, area under the curve (AUC) (95% CI) values were higher for the VVR score than those for other clinical scores measured. Similarly, at the 48th h, AUC (95% CI) values were higher for the VVR score than those for the other clinical scores measured for the length of stay and mechanical ventilation. Discussion The VVR score at 48 h postoperation was found to best correlate with prolonged pediatric intensive care unit (PICU) stay, length of hospitalization, and ventilation duration, with the greatest AUC-receiver operating characteristic (0.715, 0.723, and 0.843, respectively). The 48-h VVR score correlates well with prolonged ICU, hospital stay, and ventilation.